Gendered-Perspective Agile Leadership in the VUCA Era During the Covid-19 Pandemic - Ismi D. A. Nurhaeni; Asbiyal Nurdin; Prama Wiratama; Yusuf Kurniawan (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2022)
This study was to formulate a gender-responsive agile leadership model during the Covid-19 pandemic. A systematic literature review using PRISMA methods and field research on 18 purposely selected mid-level managers was conducted. The research discovers that first, agile leadership characteristics can be classified into individual and organizational dimensions. Individual characteristics include the personal values of agile leaders with good personalities. Organizational characteristics are characteristics to maintain and bring the organization to face a fast-changing and uncertain world. Second, the characteristics of gender-perspective leadership in the Covid-19 era are the commitment to change the management system, organizational culture, and the quality of leadership to promote gender equity. Finally, the Gendered-Perspective Agile Leadership model in the VUCA era during the Covid-19 pandemic is a leadership model that can quickly respond to gender issues through management system change, organizational culture, and character development of leaders oriented to individual and organizational characteristics. Individually trained leader characters are supposed to be intelligent, optimistic, communicative, accountable and compassionate, while organizationally oriented leader characters are adaptive, responsive, innovative, flexible, and transparent. This paper uses thematic analysis to fill the gap of the gendered-perspective agile leadership model by exploring the characteristics of gendered- perspective agile leadership in the COVID- 19 era.